Kontribusi Pola Asuh Orang Tua Terhadap Minat Belajar Siswa Kelas X SMK N 9 Padang - Meisya Sabilla; Linda Fitria; Rini Sefriani (Universitas Putra Indonesia YPTK Padang, 2021)
This study aims to describe the contribution of parenting to students' interest in learning. Parenting patterns are all the ways and actions taken by parents in carrying out their responsibilities as parents. While interest in learning is a sense of preference and a sense of attachment to a thing or activity, without anyone touching. This study aims to determine the magnitude of the contribution of parenting patterns to the learning interest of class X students in the even semester of SMK Negeri 9 Padang for the 2020/2021 academic year. The method used in this study is quantitative with the type of research that is correlational, the population of this study amounted to 420 people who were registered with a sample of 204 people who were registered in class x for the 2020/2021 academic year. The sampling technique used is purposive sampling technique. So that the number of samples obtained is 204 people. The instrument in this study was a Likert scale questionnaire. Data analysis was performed using statistical programs on IBM Statistical 20 computers and Microsoft Excel. Based on the results of data processing, it is obtained that the rcount value is 0.498 with an rtable value of 0.138 because the rcount value is greater than the rtable value (0.498> 0.138), it can be concluded that there is a significant correlation with the direction between the contribution of parenting parents to contribute to student learning interest, with the contribution value is 25%, which means that the parenting pattern of parents' interest in learning is in the low category.